Rule-Based Energy Management System to Enhance PV Self-Consumption in a Building: A Real Case - Camblong, Haritza; Zapirain, Irati; Curea, Octavian; Ugartemendia, Juanjo; Boussaada, Zina; Zamora, Ramon (MDPI AG, 2024)
The building sector has an important role in the decarbonization of energy. Buildings energy management systems can act on flexible loads to contribute to the integration of renewable energies. This article presents the design, implementation and evaluation of a rule-based energy management systems (RB-EMS) in the frame of a collective self-consumption (CSC) system based on photovoltaic (PV) energy in the Technology Park of Izarbel, in Bidart, France. The RB-EMS acts on the heat ventilation and air conditioning (HVAC) system of one of the buildings involved in the CSC in order to maximize the PV energy self-consumption rate (SCR). Internet of things (IoT) has been developed and implemented in order to retrieve consumption, production and temperature data, and to be able to act on the HVAC. A new 5-step methodology has been developed to design and adjust the RB-EMS. This methodology is mainly based on tests carried out to find the relationship between ON/OFF states of the internal units of the HVAC and the heat pumps’ consumption. Finally, the RB-EMS is tested in heating operating mode. The results show that the RB-EMS allows obtaining a SCR of 89%, and that the users comfort limits are respected.
Keywords: 33 Built Environment and Design; 3301 Architecture; 7 Affordable and Clean Energy; 13 Climate Action; 02 Physical Sciences; 09 Engineering; 33 Built environment and design; 40 Engineering; 51 Physical sciences